Pengembangan Media Bigbook Berbasis Multimedia Untuk Melatih Kemampuan Membaca Permulaan Siswa Kelas II SD Negeri 101965 Kotasan T.A 2023/2024 - Putri Lestari Br Sembiring; Mastari Ramadhani (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This research aims to determine the development of multimedia-based bigbook media to train the beginning reading skills of class II students at SD Negeri 101965 Kotasan. To determine the feasibility of developing learning media at the beginning of reading for class II at SD Negeri 101965 Kotasan in the form of a bigbook. This type of research is Research and Development (R&D). The subjects of this research were class II students at SD Negeri 101965, totaling 39 students, consisting of 17 female students and 13 male students. The research results show that the media developed meets the requirements for use as learning media. Based on material expert assessment states that the feasibility percentage is 92% "Very Eligible" criteria. The media expert's assessment states that the percentage Eligibility is 90% "Very Eligible" criteria. Student responses are based on tests try the percentage of eligibility obtained is 4% criteria "Very Worthy". Based on the teacher's response, the eligibility percentage is 96% of the criteria “Very Worth It”. The media has been validated by media and material experts and stated very suitable for use as a learning medium in initial reading lessons for class II at SD Negeri 101965 Kotasan.